1990
DOI: 10.3382/ps.0690313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Energy Electron Irradiation of Chicken Meat on Thiobarbituric Acid Values, Shear Values, Odor, and Cooked Yield

Abstract: Experiments were conducted to determine whether electron-beam irradiation would affect shear values, yield, odor, and thiobarbituric acid (TBA) values of chicken tissues. Broiler breasts (pectoralis superficialis) and whole thighs were irradiated with an electron-beam accelerator at levels to produce adsorbed doses of 100, 200, and 300 krads on the surface of the sample. The thigh samples were stored for 2, 4, and 8 days before testing for TBA values. The depth to which the radiation had penetrated the pectora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 6 publications
4
13
0
Order By: Relevance
“…Patterson and Stevenson (1995) reported dimethyl trisulphide as the most potent off-odour compound in irradiated raw chicken followed by cis-3-and trans-6-nonenal, oct-1-en-3-one and bis(methylthio)methane. It has been reported that irradiated raw chicken meat gave off a bloody and sweet aroma (Heath et al, 1990). Increase in irradiation-induced sulphur-containing volatiles appears to be the result of radiolytic degradation of sulphur-containing amino acids (Ahn, 2002) and lipid oxidation , which produces cabbage-like or rotten vegetable putrid odours.…”
Section: Irradiation and High Pressurementioning
confidence: 99%
“…Patterson and Stevenson (1995) reported dimethyl trisulphide as the most potent off-odour compound in irradiated raw chicken followed by cis-3-and trans-6-nonenal, oct-1-en-3-one and bis(methylthio)methane. It has been reported that irradiated raw chicken meat gave off a bloody and sweet aroma (Heath et al, 1990). Increase in irradiation-induced sulphur-containing volatiles appears to be the result of radiolytic degradation of sulphur-containing amino acids (Ahn, 2002) and lipid oxidation , which produces cabbage-like or rotten vegetable putrid odours.…”
Section: Irradiation and High Pressurementioning
confidence: 99%
“…Irradiation, while a powerful food safety tool, has been implicated in accelerating oxidation and producing free radicals, thereby changing the oxidative potential of meat products (Jo and Ahn, 2000;Nam and Ahn, 2003). Irradiation can influence the color of fresh meat (Nanke et al, 1998), yet reports of its effects on tenderness have been mixed (Heath et al, 1990;Yoon, 2003). However, few studies have been performed on early postmortem product.…”
Section: Introductionmentioning
confidence: 99%
“…Thayer et al (22) reported that irradiation dose, processing temperature, and packaging conditions strongly influence microbial and nutritional quality of meat. Heath et al (14) reported that irradiating uncooked chicken breast and thigh at 2 or 3 kGy produced a hot fat, burned oil, or burned feathers odor that remained after the thighs were cooked. Hashim et al (22) reported that irradiating uncooked chicken breast and thigh produced a characteristic bloody and sweet aroma that remained after the thighs were cooked, but was not detectable after the breasts were cooked.…”
Section: Introductionmentioning
confidence: 99%